Kandungan Hara Tanah dan Tanaman Karet Menghasilkan Terhadap Pemberian Tandan Kosong Kelapa Sawit (TKKS) dan Jumlah Lubang Biopori - Ando Tikkos M Simbolon; Chairani Hanum; Ratna Rosanty Lahay (Universitas Sumatera Utara, 2015)
Nutrient conten of the soil and rubber produced by giving empty oil palm fruit bunches and the number of biopori holes. Rubber is a kind of plant which is important and can increase income and social prosperity. This research cond ucted at Silau Dunia garden PTPN III Serdang Bedagai on August – December 2014 by using random missed block design with two factors. The first factor is empty oil palm bunches contained : 0, 1, 2 and 3 kg for each biopori and the second factor is the number of holes consisted : 4, 8 and 12, With three replication. The results of this research showed that interaction application empty fruit bunch and number of biopori increase of N soil, N leaf and Cholorofil number.Keywords: Biopori, palm empty bunches, RubberABSTRA